Wildfire exposure during pregnancy and the risk of adverse birth outcomes: A systematic review. (November 2021) - Amjad, Sana; Chojecki, Dagmara; Osornio-Vargas, Alvaro; Ospina, Maria B.
Highlights: There is low certainty of evidence that wildfire exposure during pregnancy is linked to reduced birth weight. There is very low certainty of evidence that maternal exposure to wildfire in any trimester is associated with preterm birth. Well-designed comprehensive studies are needed to better understand the perinatal effects of wildfires. Abstract: Background: Maternal wildfire exposure (e.g., smoke, stress) has been associated with poor birth outcomes with effects potentially mediated through air pollution and psychosocial stress. Despite the recent hike in the intensity and frequency of wildfires in some regions of the world, a critical appraisal of the evidence on the association between maternal wildfire exposure and adverse birth outcomes has not yet been undertaken. We conducted a systematic review that evaluated the scientific evidence on the association between wildfire exposure during pregnancy and the risk of adverse birth outcomes. Methods: Comprehensive searches in nine bibliographic databases were conducted from database inception up to June 2020. Observational epidemiological studies that evaluated associations between exposure to wildfire during pregnancy and adverse birth outcomes were eligible for inclusion. Studies were assessed using the National Toxicology Program's Office of Health Assessment and Translation (NTP OHAT) risk of bias tool and certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) framework. Screening of retrieved articles, data extraction, and risk of bias assessment were performed by two independent reviewers. Study results were synthesized descriptively. Results: Eight epidemiological studies conducted in four countries and involving 1, 702, 252 births were included in the review. The exposure to wildfire during pregnancy was assessed in individual studies by measurement of PM2.5 (n = 2), PM10 (n = 1), Total Ozone Mapping Spectrometer (TOMS) aerosol index (n = 1), heat spots (n = 1), and by proximity of maternal residence to wildfire-affected areas (n = 3). There is some evidence indicating that maternal wildfire exposure associates with birth weight reduction (n = 7) and preterm birth (n = 4), particularly when exposure to wildfire smoke occurred in late pregnancy. The association between wildfire exposure and small for gestational age (n = 2) and infant mortality (n = 1) was inconclusive. Conclusion: Current evidence suggests that maternal exposure to wildfire during late pregnancy is linked to reduced birth weight and preterm birth. Well-designed comprehensive studies are needed to better understand the perinatal effects of wildfires.